THE INFLUENCE OF DIFFERENTIATED FERTILISATION ON THE SUGAR LEVEL IN THE MUST, FOR THE ALIGOTE AND FETEASCA ALBA VARIETIES, UNDER THE CONDITIONS OF THE IASI VINEYARD - Nicoleta Luminita PARASCHIV; Mariana VOLF; Elena Liliana CHELARIU (Journal of Applied Life Sciences and Environment)
Wine soils from the country’s main vineyards contain 0.05-0.25 g total per 100 g soil, 0.9-20 mg /100 g soil and 6.5-36 mg /100 g soil. The amount of fertiliser that the plant will use – the degree of use – depends on the age of the stumps, the type of rootstock and the planned production. Acting as a factor for the intensification of production, mineral fertilisers, used as a complement to organic fertilisation, contribute not only to maintaining and increasing soil fertility but also to the quantitative and qualitative growth of production. Since the natural reserves of nutrients are limited, the application of natural and mineral fertilisers, scientifically based and differentiated according to the concrete pedoclimatic conditions, is of particular importance from an ecological and economic point of view. The research undertaken highlighted that the use of chemical fertilisers, in different dosages and ratios, favourably influenced the accumulation of sugar in the must for both varieties, with values that were between 178 g/L sugars for the Aligote variety and 170.7 g/L for Feteasca alba. The- relationship positively influenced the accumulation of sugars for both varieties, 177.4 g/L sugars for the Aligote variety and 171.3 g/L for Feteasca alba.